Suitability of transiently expressed antibodies for clinical studies: product quality consistency at different production scales. Issue 1 (31st December 2022) - Rodriguez-Conde, Sara; Inman, Sophie; Lindo, Viv; Amery, Leanne; Tang, Alison; Okorji-Obike, Uche; Du, Wenjuan; Bosch, Berend-Jan; Wichgers Schreur, Paul J.; Kortekaas, Jeroen; Sola, Isabel; Enjuanes, Luis; et al.
ABSTRACT: Transgenic human monoclonal antibodies derived from humanized mice against different epitopes of the Middle East respiratory syndrome coronavirus (MERS-CoV), and chimeric llama-human bispecific heavy chain-only antibodies targeting the Rift Valley fever virus (RVFV), were produced using a CHO-based transient expression system. Two lead candidates were assessed for each model virus before selecting and progressing one lead molecule. MERS-7.7G6 was used as the model antibody to demonstrate batch-to-batch process consistency and, together with RVFV-107-104, were scaled up to 200 L. Consistent expression titers were obtained in different batches at a 5 L scale for MERS-7.7G6. Although lower expression levels were observed for MERS-7.7G6 and RVFV-107-104 during scale up to 200 L, product quality attributes were consistent at different scales and in different batches. In addition to this, peptide mapping data suggested no detectable sequence variants for any of these candidates. Functional assays demonstrated comparable neutralizing activity for MERS-7.7G6 and RVFV-107-104 generated at different production scales. Similarly, MERS-7.7G6 batches generated at different scales were shown to provide comparable protection in mouse models. Our study demonstrates that a CHO-based transient expression process is capable of generating consistent product quality at different production scales and thereby supports the potential of using transient gene expression to accelerate the manufacturing of early clinical material.